Impact of Religion in Maintaining the Stability of a Country: Comparative Study Between Soeharto’s Era and Prabowo’s Era - Mohammad Ridhan Alhafidz; Anel Nailul (Institut Studi Islam Muhammadiyah Pacitan, 2026)
ABSTRACT This research will explain the situation of religion during the Suharto era and the Prabowo era. President Suharto considered religion to be a threat to national stability, so he restricted religious literature to government publications to prevent seditious doctrines from entering through religion, while President Prabowo considered religion to be one aspect of maintaining national stability. This study will explain the role of religion in Indonesia's independence and the views of President Suharto and President Prabowo on religion. This study will also explain the relationship between religion and the state. These issues will add to the insight and understanding of the differences in the views of President Suharto and President Prabowo on religion. This study will use descriptive and analytical methods. This brief study will provide an analysis that can be developed in religious life in Indonesia as a guardian of state stability.